Pembelajaran Struktur Data Berbasis Visualisasi dengan Menggunakan Visualgo.Net - Muhammad Sholeh; RR. Yuliana Rachmawati (Penerbit Goodwood, 2022)
Purpose: The purpose of the activity include preparing Prambanan Sleman High School students who will take part in the National Science Competition, especially in the field of Informatics. One of the preparations made is assistance on data structure material. Data structure is an important material in learning programming. Method: The activity method is provided by providing assistance in the process of providing data structure material that is adjusted to the syllabus including primitive data types, arrays, strings, stacks, queues, binary heaps, disjoint sets and segment trees. The material is packed with visualization-based explanations. Visualization learning is given using the visualgo.net application. Result: By using visualization, students who take part in the mentoring have experience of the process and logic in creating and understanding data structures. The results of the implementation, students get data structure material based on visualgo.net and explained how the data structure algorithm process is related to visualization-based. Conclusion: Data structure learning is given by using the visualgo.net application. Visualgo.net can help students in the process of studying data structure material. Visualization-based learning in studying data structure material is very helpful in the process of learning programming material. In this activity, students get an explanation of the algorithm used in the data structure, both with theory and with visualization-based explanations.